Revisiting the Role of Positive Emotion as a Cognitive Enhancer: Empirical Evidence from Visuospatial Working Memory Performance - Fitri Natalia; Juliana Marlin Yusrianti Benu; Indra Yohanis Kiling; Mariana Dinah Charlota Lerik (Universitas Katolik Soegijapranata, 2025)
Working memory is a limited-capacity cognitive system responsible for the temporary storage, processing, and manipulation of information to support various cognitive tasks. One factor that may influence working memory performance is emotion. This study aimed to examine the effect of positive emotion on visuospatial working memory capacity among university students. A quasi-experimental design with a randomized pretest–posttest control group design was employed. Thirty-two undergraduate students (aged 18–23 years; 20 females and 12 males) without a history of neurological or psychiatric disorders participated in the study. The intervention involved the presentation of a fifthteen minute video designed to induce positive emotion, while the control group viewed a neutral video of the same duration. The Self-Assessment Manikin (SAM) was used to assess emotional states, and the Corsi Block Tapping Task (CBTT) was administered to measure visuospatial working memory capacity. Data were analyzed using an independent samples t-test. The results indicated no significant difference in the improvement of CBTT scores between the experimental and control groups, t(30)= 0.38, p = .71, p .05.These findings indicate that positive emotion does not have a significant effect on visuospatial working memory capacity among university students.